REVISITING THE 2005 EARTHQUAKE PARAPLEGICS: WHAT HAS CHANGED IN A DECADE? - Rathore, Farooq Azam (Journal of Ayub Medical College Abbottabad, 2015)
Oct 2005 earthquake was a great tragedy, which resulted in hundreds of paraplegics. This was the largest number of Spinal cord injuries (SCI) reported in a natural disaster. The health care system ofPakistanwas not well equipped to handle such a large number of major neurological disabilities. Despite these limitations, the initial response was adequate, aided by involvement and guidance from foreign medical teams skilled in management of SCI. It also resulted in strengthening and establishment of better centers for management of SCI. We hoped that this enthusiasm would continue and result in better rehabilitation and community re-integration of these individuals with a long-term disability. Unfortunately, this goal did not materialize. This editorial highlights the current situation of 2005 paraplegics, discusses the shortcomings in long term planning and presents some viable solutions for comprehensive management and rehabilitation of these SCI patients.